The Portrayal of Stereotypical Gender Roles In Harry Potter Series - Nasrullah, Nasrullah; Supriyadi, Moh. (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2024)
The Harry Potter series is one of the most phenomenal works of children's literature. It has attracted public attention since it was first published in 1997 and has received increasing attention as time goes by. This study is purposed to investigate whether the Harry Potter series, as one of the most successful, popular, and influential works of children’s literature, is incapable of challenging stereotypes of gender. Contrary to the popular belief that says otherwise, this study demonstrates the part when the characters of this series are continuously behaving and interacting with each other using the typical gender traits. Several scholars may claim that this series is gender equal and gives the same opportunity to both boys and girls. The author states that she has the intention of gender equality. However, as the story is being conducted, it is shown that this series is still unable to challenge gender stereotypes